Multi-perspective evaluation of integrated active cooling systems using fuzzy decision making model - Abdullah Hussein Abdullah Al-Amoodi (Tanjung Malim, 2023)
Multi-perspective evaluation of integrated active cooling systems using fuzzy decision making model by Abdullah Hussein Abdullah Al-Amoodi